Novel two‐lead cardiac resynchronization therapy system provides equivalent CRT responses with less complications than a conventional three‐lead system: Results from the QP ExCELs lead registry. (1st June 2020) - Shaik, Naushad A.; Drucker, Michael; Pierce, Christopher; Duray, Gabor Z.; Gillett, Shane; Miller, Crystal; Harrell, Camden; Thomas, George
Abstract: Introduction: The novel two‐lead cardiac resynchronization therapy (CRT)‐DX system utilizes a floating atrial dipole on the implantable cardioverter‐defibrillator lead, and when implanted with a left ventricular (LV) lead, offers a two‐lead CRT system with AV synchrony. This study compared complication rates and CRT response among subjects implanted with a two‐lead CRT‐DX system to those subjects implanted with a standard three‐lead CRT‐D system. Methods and Results: A total of 240 subjects from the Sentus QP—Extended CRT Evaluation with Quadripolar Left Ventricular Leads postapproval study were selected to identify 120 matched pairs based on similar demographic characteristics using a Greedy algorithm. The complication‐free rate was evaluated as the primary endpoint. All‐cause mortality, heart failure hospitalizations, device diagnostic data, New York Heart Association (NYHA) class improvement, and defibrillator therapy were evaluated from clinical data, in‐office interrogations, and remote monitoring throughout the follow‐up period. Complication‐free survival favored the CRT‐DX group with 92.5% without a major complication compared to 85.0% in the CRT‐D cohort ( P = .0495; 95% confidence interval: 0.1%‐14.9%) over a mean follow‐up of 1.3 and 1.4 years, respectively. Incidence of all‐cause mortality, heart failure hospitalizations, NYHA changes at 6 months postimplant, and percent of LV pacing during CRT therapy were similar in both device cohorts. Inappropriate shocks were more frequent in the CRT‐D cohort with 5.8% of subjects receiving an inappropriate shock vs 0.8% in the CRT‐DX cohort. Conclusion: The results of this subanalysis demonstrate that the CRT‐DX system can provide similar CRT responses and significantly fewer complications when compared to a similar cohort with a conventional three‐lead CRT‐D system.